Antimicrobial Resistance in Gram-Negative Hospital Isolates: Results of the Turkish HITIT-2 Surveillance Study of 2007 - ALTINKANAT GELMEZ, GÜLŞEN (TAYLOR & FRANCIS LTD, 2009)
Resistance rates to amikacin, ciprofloxacin, ceftazidime, cefepime, imipenem, cefoperazone/sulbactam and piperacillin/tazobactam in Escherichia coli (n = 438), Klebsiella pneumoniae (n = 444), Pseudomonas aeruginosa (n = 210) and Acinetobacter baumanni (n =200) were determined with E-test in a multicenter surveillance study (HITIT-2) in 2007. ESBL production in Escherichia coli and K. pneumoniae was investigated following the CLSI guidelines. Overall 42.0% of E.coli and 41.4% of K. pneumoniae were ESBL producers. In E. coli, resistance to imipenem was not observed, resistance to ciprofloxacin and amikacin was 58.0% and 5.5% respectively. In K. pneumoniae resistance to imipenem, ciprofloxacin and amikacin was 3.1%, 17.8% 12.4% respectively. In P. aeruginosa the lowest rate of resistance was observed with piperacillin/tazobactam (18.1%). A. baumanni isolates were highly resistant to all the antimicrobial agents, the lowest level of resistance was observed against cefoperazone/sulbactam (52.0%) followed by imipenem (55.5%). This study showed that resistance rates to antimicrobials are high in nosocomial isolates and show variations among the centers.
Keywords: Antimicrobial resistance; ESBL; Gram-negative bacteria; beta-lactamase inhibitor; E.coli; K. pneumoniae; P. aeruginosa; A. baumannii; SPECTRUM BETA-LACTAMASES; KLEBSIELLA-PNEUMONIAE; ESCHERICHIA-COLI; TURKEY; SUSCEPTIBILITY; CARBAPENEMASES; OXACILLINASE; PREVALENCE; MECHANISMS; ORGANISMS